Nutrition-related considerations for health and performance in female basketball players: a narrative review - Miguel Ortega, Álvaro; Calleja González, Julio; Mielgo Ayuso, Juan (My University, 2023)
Basketball is a popular team sport worldwide. Nutrition is one of the key aspects for the optimization of performance and subsequent recovery. Female athletes have unique nutri tional requirements as a result of daily training and competition, in addition to the specific de mands of gender-related physiological changes. However, inadequate, or erroneous nutritional behaviours are commonly observed. Thus, the aim of our work is to provide concise nutritional recommendations for female basketball players. Based on a review of the literature, there is limited evidence that comprehensively assesses health attributes as well as behaviours, habits, and nutritional knowledge of physical activity by gender in basketball players. Recent research highlights the need for nutritional strategies to develop tools to help manage energy deficiency in women¿s sports. We suggest that individual adjustment of dietary energy value is the key factor in the physical performance of female basketball players; information that could be used to optimize the training process and health maintenance. The recommended intake for athletes involved in moderate levels of training, such as elite basketball players (2-3 h/day for 5-6 times/week), is 50-80 kcal·(kg·day)-1, with specific recommendations of 1.6-1.8 g·(kg·day)-1 protein. For physically active women, it is recommended that 1.2-2 g·(kg·day)-1 of protein be consumed, with fat intake of 20-35% of total kilocalories and 5-8 g·(kg·day)-1 of carbohydrate to adequately meet performance demands. Keywords : basketball, women, nutrition, health, team sport